(untitled) (Damascus University Journal for engineering sciences, 2024)
The process of reconstructing the destroyed areas in Syria is linked to a number of laws, legislation, and foundations that regulate the planning of areas in order to achieve justice, access to services, adequate housing, and others. The literature on city planning emphasizes the role of urban spatial structures in re-visioning cities and assessing their development in line with the evolution of the contexts of their societies. These structures are mainly related to population, density, style of life, needs, etc... therefore, it must be pointed out that the planning foundations applied in the planning of residential communities in general, as well as laws and legislations timidly address the cultural and social factor. that impact on the displacement and migration, mixing place and the urban fabric patterns as well as the shape of the gatherings changed after the arrival of the displaced from the devastated areas due to the war, which clearly warns of the danger of identity loss and urban dispersal. This research analysis the importance of enhancing social cohesion and its integration with the urban fabric in the reconstruction phase by discussing the following question: Can the social and cultural factor be linked to the reconstruction of urban structures within the master plans? This research discusses the relationship between social structures and master plans for cities in general, and in Homs, Syria in particular, which has spatial and social peculiarity as a central area and an important location on the commercial and economic axis. It studies the urban structure and its relationship with the local community, the concept of the urban system and its specific and associated levels, determining the spatial interactions between cities, their classifications and forms, and emphasizing the importance of their role in shaping urban system, in order to develop urban structures and its classification according to social organization and historical axis. The methodology of this research applies the descriptive and inductive approach in its theoretical part related to concepts, relationships and the analytical method in a deductive way to reach the urban social structure relationship matrix. Also, statistical analysis related to the social statement in the study area. The research aims to integrate the social factors on the urban structure and on urban system during the study of master plans to strengthen the urban social structure.